2022
DOI: 10.1039/d2nj01291j
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of the column chromatographic process of Phellodendri Chinensis Cortex part I: end-point determination based on near-infrared spectroscopy combined with machine learning

Abstract: As a widely used technique in the area of natural medicine, column chromatographic process lacks appropriate process monitoring methods. In this work, near infrared spectroscopy was applied to develop a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This finding was in good accordance with a previously conducted study, which found that alkaloids were eluted fastest in the period from the 60th to 70th min. 10 It can be seen from Fig. 10 that the trajectories of the PC1 scores and DModX of the 16th batch obviously exceeded the control ranges.…”
Section: Monitoring Of Batches With Abnormal Elution Flow Ratesmentioning
confidence: 92%
See 3 more Smart Citations
“…This finding was in good accordance with a previously conducted study, which found that alkaloids were eluted fastest in the period from the 60th to 70th min. 10 It can be seen from Fig. 10 that the trajectories of the PC1 scores and DModX of the 16th batch obviously exceeded the control ranges.…”
Section: Monitoring Of Batches With Abnormal Elution Flow Ratesmentioning
confidence: 92%
“…Before the formal elution test started, the macroporous resin was pretreated and the concentrated solution was obtained according to the methods introduced in part I of this work. 10 The added volume of concentrated solution, the elution flow rate, and the ratio of ethanol in the eluent were selected as the factors of interest, which were varied between the settings at three different levels based on the results of the preliminary experiments. 10 A total of 17 experimental runs were obtained after the design (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method has the advantages of fast learning speed and good generalization performance. [18][19][20] Taking the Raman spectra of the samples of various brands collected with the integration time of 80 s as an example, the original data were first introduced into an extreme learning machine algorithm, with 72% of the samples as test sets (54 samples) and 28% as training sets (21 samples). The sample selection was random and ran 200 times.…”
Section: Pretreatment Analysis Of Raman Spectra Of Cheese Productsmentioning
confidence: 99%